Protein phosphorylation in bacterial signal transduction - Kobir, Ahasanul; Shi, Lei; Boskovic, Ana; Grangeasse, Christophe; Franjevic, Damjan; Mijakovic, Ivan (Biochimica et biophysica acta, 2011)
Protein phosphorylation has emerged as one of the major post translational modifications in bacteria, involved in regulating a myriad of physiological processes. In a complex and dynamic system such as the bacterial cell, connectivity of its components accounts for a number of emergent properties. This article is part of a Special Issue entitled: Systems Biology of Microorganisms. This review focuses on the implications of bacterial protein phosphorylation in cell signaling and regulation and highlights the connections and cross talk between various signaling pathways: bacterial two-component systems and serine/threonine kinases, but also the interference between phosphorylation and other post-translational modifications (methylation and acetylation). Recent technical developments in high accuracy mass spectrometry have profoundly transformed proteomics, and today exhaustive site-specific phosphoproteomes are available for a number of bacterial species. Nevertheless, prediction of phosphorylation sites remains the main guide for many researchers, so we discuss the characteristics, limits and advantages of available phosphorylation predictors. The advent of quantitative phosphoproteomics has brought the field on the doorstep of systems biology, but a number of challenges remain before the bacterial phosphorylation networks can be efficiently modeled and their physiological role understood. This article is part of a Special Issue entitled: Systems Biology of Microorganisms. ► Protein phosphorylation regulates bacterial housekeeping processes and virulence. ► Bacterial phosphorylation networks exhibit connectivity and signal integration. ► Mass spectrometry can detect and quantify >100 phosphorylation sites per bacterium. ► Bacterial phosphorylation sites are not conserved; kinases show relaxed specificity. ► Bacterial phosphorylation predictors exist, but are limited in prediction accuracy.